Immune Disregulation in Cutaneous Squamous Cell Carcinoma of Patients with Recessive Dystrophic Epidermolysis Bullosa: A Single Pilot Study - Angela Filoni; Gerolamo Cicco; Gerardo Cazzato; Anna Bosco; Lucia Lospalluti; Marco Tucci; Antonietta Cimmino; Caterina Foti; Andrea Marzullo; Domenico Bonamonte (Life, 2022)
Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most devastating complications of recessive dystrophic epidermolysis bullosa (RDEB). We recently demonstrated a reduction in immune cell peritumoral infiltration in RDEB patients with cSCC, together with a reduction in CD3+, CD4+, CD68+ and CD20 lymphocytes as compared to primary and secondary cSCC in patients without RDEB. Recently, new molecules, such as high mobility group box 1 (HMGB1), T cell immunoglobulin, mucin domain 3 (TIM-3) and Heme oxygenase-1 (HO-1), have been shown to play a role in antitumoral immunity. Objective: Patients with RDEB are known to be at increased risk of developing skin cancers, including the dreaded squamous cell carcinoma of the. Tendentially, cSCCs that arise in the context of EBDR are more aggressive and lead to statistically significant bad outcomes compared to cSCCs developed on the skin of patients without EBDR. In an attempt to study the microenvironment of these lesions, we conducted an immunohistochemical analysis study of proteins that could be actively involved in the genesis of this type of malignant neoplasms. Methods: In this retrospective study, the OH1-HMGB1-TIM3 activation axis, as correlated to the T lymphocytes cell count, was assessed in biopsy samples from 31 consecutive cases consisting of 12 RDEB patients with cSCC, 12 patients with primary cSCC and 7 RDEB patients with pseudoepitheliomatous cutaneous hyperplasia. Parametric Student’s t-test was applied for normally distributed values, such as CD4+ and CD8+, and non-parametric Mann–Whitney test for non-normally distributed values, such as HMGB-1, TIM-3 and HO-1. Results: In RDEB patients with cSCC and with pseudoepitheliomatous hyperplasia, the expression of CD4 T helper lymphocytes was lower than in the peritumoral infiltrate found in primary cSCC. CD8 cytotoxic T lymphocytes were increased in primary cSCC compared to the other two groups. An increased HMGB1 expression was evident in both primary and RDEB cSCC. TIM3 expression was higher in RDEB patients with cSCC compared to the other two groups. A significantly reduced immunohistochemical expression of HO-1 was evident in the tumoral microenvironment of cSCC-RDEB as compared to primary cSCC. Conclusions: These data suggest that a reduced immune cell peritumoral infiltration in RDEB patients could be responsible, in the complexity of the mechanisms of carcinogenesis and host response, of the particular aggressiveness of the cSCC of RDEB patients, creating a substrate for greater local immunosuppression, which, potentially, can “open the doors” to development and eventual metastasis by this malignant neoplasm.